(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Cardiovascular diseases (CVD) represent the leading cause of global mortality, significantly impacting quality of life and healthcare costs. Early identification of risk factors associated with CVD and their potential mediators is crucial for developing more effective prevention strategies and establishing therapeutic goals aimed at better clinical outcomes and preventing adverse events. Evidence indicates that early menarche is associated with an increased risk of developing CVD in adulthood. Therefore, considering menarche age during clinical evaluations may be an important factor in identifying women with a higher likelihood of developing CVD and its risk factors throughout life. Objectives: To review the literature on the relationship between early menarche and cardiovascular risk in adult women. Methods: Scientific articles in English and Portuguese published up to 2023 were selected from the online databases PubMed, Scopus, and SciELO, using the descriptors “early menarche, hypertension, dyslipidemia, diabetes, and obesity” with the Boolean operator “and.” Results: This review explores key aspects related to metabolic and hormonal changes associated with early puberty onset and its connection with major CVD risk factors such as obesity, hypertension, diabetes, and dyslipidemia. Conclusion: Obesity plays a significant role as a mediator in the influence of early maturation on other risk factors. However, it is important to consider that other variables may influence this relationship, highlighting the need for further research to gain a more comprehensive understanding of the association between early menarche and CVD risk factors.